Theeffect Of Using Pcture Series On Young Learners’ Vocabulary Mastery - Siti Aisyah Ginting (BAHAS, 2018)
Abstract The aim of the research is to know the effect of using picture series on young learners’ vocabulary mastery at the third grade of MIS Luqman Al Hakim TanjungMorawa2016/2017. The design of this research was experimental method that consists of pre-test (X1), treatment (T) and post-test (X2). Population of this research was the whole third grade students in MIS Luqman Al Hakim TanjungMorawa. The sample of this research was the Class III-Utsman Bin Affan consist 20 students. In collecting the data, the researcher used pre-test and post-test. Pre-test is given to know young learners’ vocabulary mastery before getting treatment by using picture series. Post-test is given to know young learners’ vocabulary mastery after getting treatment by using picture series. The treatment has been given as many three times to the sample. After the data collected, it was analyzed by using t-test. The result showed the value of‘t’ observed = 3.085 and ‘t’ table = 2.024. Therefore, the value of ‘t’ table exceeds ‘t’ observed value. It means that Ho has no influence on young learners’ vocabulary mastery and Ha has influence on young learners’ vocabulary mastery. In other words, the picture series was effective in teaching vocabulary on students of class III-Utsman bin AffanMIS Luqman Al Hakim TanjungMorawa.Keywords:Picture Series, Young Learners, Vocabulary Mastery